Taming the Poisonous Mercury, Toxicity, and Safety in Tibetan Medical Practice - Gerke, Barbara (Heidelberg Studies on Transculturality, 2021)
This rich ethnographic and socio-historical account uncovers how toxicity and safety are expressed transculturally in a globalizing world. For the first time, it unpacks the "pharmaceutical nexus" of mercury in Tibetan medicine (Sowa Rigpa) where, since the thirteenth century, it has mainly been used in the form of tsotel. Tsotel, an organometallic mercury sulfide compound, is added in small amounts to specific medicines to enhance the potency of other ingredients. In concordance with tantric Buddhist ideas, Tibetan medical practitioners confront and tame poisonous substances, and instead of avoiding or expelling them, transform them into potent medicines and elixirs. Recently, the UN Environment Programme's global ban on mercury, the Minamata Convention, has sparked debates on the use of mercury in Asian medicines. As Asian medical traditions increasingly intersect with biomedical science and technology, what is at stake when Tibetan medical practitioners in India and Nepal, researchers, and regulators negotiate mercury's toxicity and safety? Who determines what is "toxic" and what is "safe," and how? What does this mean for the future of traditional Asian medical and pharmaceutical practices?